2016
DOI: 10.1080/02670836.2015.1115244
|View full text |Cite
|
Sign up to set email alerts
|

Nitriding of Fe–18Cr–11Mn powders using mechanical alloying method through aerating nitrogen circularly

Abstract: Mechanical alloying (MA) method was applied to nitride Fe–18Cr–11Mn stainless steel powders through aerating nitrogen circularly. Both the MA process and increasing nitrogen pressure circularly caused the expansion of nitrogen solubility in Fe. The microstructure of powders was affected by the milling time. The phase transformation of α-Fe to γ-Fe occurred during the MA process. The grain size of powder decreased, while the internal lattice strain increased by increasing the milling time and cycles of aerating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Especially for the restoring of large components, a possible cost benefit can be achieved by omitting the additional step.A new approach for the enhancement of coating properties is the direct thermochemical treatment of the thermal-spraying feedstock. Different approaches for the nitriding of steel powder have been investigated [13,14]. However, no successful formation of an S-phase in austenitic steel powder has been achieved yet.…”
mentioning
confidence: 99%
“…Especially for the restoring of large components, a possible cost benefit can be achieved by omitting the additional step.A new approach for the enhancement of coating properties is the direct thermochemical treatment of the thermal-spraying feedstock. Different approaches for the nitriding of steel powder have been investigated [13,14]. However, no successful formation of an S-phase in austenitic steel powder has been achieved yet.…”
mentioning
confidence: 99%
“…For large components, an economical opportunity for partial or complete coating can be developed. Various approaches to nitride steel powder have been investigated [13,14]. Lindner et al successfully demonstrated S-phase formation in austenitic steel powder.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach for the treatment of components is the solution hardening of feedstock materials for the coating process. Various approaches to nitride steel powder have been investigated [13,14]. Lindner et al successfully demonstrated S-phase formation in austenitic steel powder.…”
Section: Introductionmentioning
confidence: 99%